2019
DOI: 10.1038/s41598-019-47993-w
|View full text |Cite
|
Sign up to set email alerts
|

KUS121, a valosin-containing protein modulator, attenuates ischemic stroke via preventing ATP depletion

Abstract: Reduced adenosine triphosphate (ATP) levels in ischemic stroke constitute an upstream contributor to neuronal cell death. We have recently created a small chemical, named Kyoto University Substance 121 (KUS121), which can reduce cellular ATP consumption. In this study, we examined whether KUS121 has neuroprotective effects in rodent cerebral ischemia models. We evaluated cell viability and ATP levels in vitro after oxygen glucose deprivation (OGD) in rat cortical primary neuronal culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Thus far, profound relations of ATP decrease, ER stress, and cell death have been repeatedly shown in several cell death-inducing cell culture conditions in various cell types, and KUS121 administration mitigated these three phenomena. Consistent with the present study, administration of KUS121 has been shown to mitigate pathologies by reducing ER stress and cell death in several animal models representing conditions such as retinitis pigmentosa 15 , myocardial infarction 16 , ischaemic stroke 20 , and Parkinson’s disease 22 . Moreover, KUS121 has been tested in phase I/II clinical trial for acute central retinal artery occlusion and shown to be safe and efficacious 23 , thereby indicating its promising candidature in the clinical therapy to inhibit the development of PTOA following cartilage injury and other conditions that have been discussed earlier.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus far, profound relations of ATP decrease, ER stress, and cell death have been repeatedly shown in several cell death-inducing cell culture conditions in various cell types, and KUS121 administration mitigated these three phenomena. Consistent with the present study, administration of KUS121 has been shown to mitigate pathologies by reducing ER stress and cell death in several animal models representing conditions such as retinitis pigmentosa 15 , myocardial infarction 16 , ischaemic stroke 20 , and Parkinson’s disease 22 . Moreover, KUS121 has been tested in phase I/II clinical trial for acute central retinal artery occlusion and shown to be safe and efficacious 23 , thereby indicating its promising candidature in the clinical therapy to inhibit the development of PTOA following cartilage injury and other conditions that have been discussed earlier.…”
Section: Discussionsupporting
confidence: 90%
“…Although the precise molecular mechanism was not fully elucidated, KUSs suppress intracellular ATP decrease by inhibiting ATPase activities of VCP, and reduces endoplasmic-reticulum (ER) stress, resulting in the inhibition of cell death 15 , 16 . KUS121 has been shown to protect against cell death in animal models of ocular diseases including retinitis pigmentosa 15 , 17 , macular degeneration 18 , and glaucoma 19 , ischemic diseases including myocardial infarction 16 , ischemic stroke 20 , and retinal artery occusion 21 and Parkinson’s disease 22 . Moreover, phase I/II clinical trials show its safety and potential effectiveness in patients with non-arteritic central retinal artery occlusion 23 .…”
Section: Introductionmentioning
confidence: 99%
“…KUSs suppress cell death under various stresses through the suppression of intracellular decrease in ATP levels and ER stress. Systemic or local administration of KUSs suppresses disease progression or deterioration in animal models of ocular diseases 14 17 , ischemic heart disease 23 , ischemic stroke 24 , and Parkinson’s disease 25 . We recently reported the therapeutic effects of KUS121 on post-traumatic cartilage damage in rats 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance of energy metabolism in the brain is a direct factor that contributes to brain injury in the early stages of IS. The brain tissue is the most oxygen-consuming in the body, therefore ischemia can easily disturb energy metabolism, reduce blood flow, limit the supply of oxygen and glucose, and reduce the production of ATP in mitochondria [15,16]. ATP deficiency leads to the inhibition of ATPdependent Na + /K + -ATP pump and Ca 2+ -ATP pump on the cell membrane as well as Na + influx and K + efflux, resulting in the depolarization of the nerve cell membrane, excessive Ca 2+ influx, and activation of phospholipases and membrane proteases.…”
Section: Disturbance Of Energy Metabolism In the Brainmentioning
confidence: 99%